An Experimental Study on Steel and Teflon Squeeze Film Dampers - Asad A. Khalid; A. Albagul; W. Faris; Godem A. Ismail (Shock and Vibration)
In this paper, the vibration analysis on Teflon and steel squeeze film dampers has been carried out. At different frequency ranges, vibration amplitude and the resonance frequency are measured. The eccentricity ratio at resonance speed has been determined. Results show that the vibration amplitude of the steel damper is 10% less at resonance compared with the Teflon damper. On the other hand, saving weight of 36% has been achieved by using the Teflon damper.